Systematic review of adverse drug reactions of ofloxacin - Kamdi, Amit S.; Kokane, Sarika D.; Bohra, Pankaj N.; Kalambe, Suvarna M. (International Journal of Basic & Clinical Pharmacology, 2018)
Adverse drug reactions (ADRs) are a major cause of morbidity and mortality in countries having limited healthcare resources. Of all the Adverse Drug Reactions, antimicrobials contribute 28% which is highest compared to the other drugs. Ofloxacin is an antimicrobial used for treating several bacterial infections. Incidence rate of adverse drug reactions (ADRs) to ofloxacin is 4.27%. Although these figures appear to be small, it is consumed for gastrointestinal infections along with ornidazole in India contributing significant burden of ADRs. However, there is no research done in past many years focusing on the adverse drug reactions of ofloxacin. This article bridges the gap of such a need. The objective of the present study was to review the adverse drug reactions related to ofloxacin in human and animal studies. Authors conducted Pubmed and Cochrane library search to review all the articles related to the adverse drug reaction of ofloxacin from 1980 to 2016. Authors got 84 articles pertaining to the adverse drug reactions of ofloxacin. Authors conclude that ofloxacin should be judiciously used as the side effect profile is increasing.